2008
DOI: 10.1364/oe.16.005965
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional grain boundary spectroscopy in transparent high power ceramic laser materials

Abstract: Using confocal Raman and fluorescence spectroscopic imaging in 3-dimensions, we show direct evidence of inhomogeneous Nd(3+) distribution across grain boundaries (GBs) in Nd(3+):YAG laser ceramics. It is clearly shown that Nd(3+) segregation takes place at GBs leading to self-fluorescence quenching which affects a volume fraction as high as 20%. In addition, we show a clear trend of increasing spatial inhomogeneities in Nd(3+) concentration when the doping levels exceeds 3 at%, which is not detected by standar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 25 publications
5
42
1
Order By: Relevance
“…This is at variance with the case of large grain ceramics in which confocal fluorescence imaging experiments have revealed a relevant Nd 3+ fluorescence quenching at the grain boundaries. 47 Since the time-resolved fluorescence comparative studies have not revealed a higher density of lattice defects in Nd:YAG ceramics with respect to Nd:YAG crystals, the reduced phonon mean free path obtained for Nd:YAG ceramics by TLS should be attributed to the phonon scattering at grain boundaries.…”
Section: B Comparative Luminescence Investigationsmentioning
confidence: 98%
“…This is at variance with the case of large grain ceramics in which confocal fluorescence imaging experiments have revealed a relevant Nd 3+ fluorescence quenching at the grain boundaries. 47 Since the time-resolved fluorescence comparative studies have not revealed a higher density of lattice defects in Nd:YAG ceramics with respect to Nd:YAG crystals, the reduced phonon mean free path obtained for Nd:YAG ceramics by TLS should be attributed to the phonon scattering at grain boundaries.…”
Section: B Comparative Luminescence Investigationsmentioning
confidence: 98%
“…To confirm this last conclusion, we examined the ceramic microstructure by confocal luminescence 33 , using the 5 D 0 → 7 F 2 transition intensity to map the spatial distribution of Eu 3+ ions (Fig. 2a).…”
Section: Inhomogeneous and Homogeneous Linewidth Are Reported In A Eumentioning
confidence: 81%
“…It is known that the increase of Nd 3+ ions concentration in the garnet matrix reduces grain boundaries mobility that results in inhibition of the grain growth for Nd 3+ :YAG [37]. At the same time, the Nd 3+ cations segregation at the grain boundaries may occurs that decreases their surface energy and mobility (due to the higher solubility limit of the impurity at the boundaries of crystallites as compared with the grain volume) [38].…”
Section: Microstructure Analysis and Optical Properties Of 0-4 At% Nmentioning
confidence: 99%